Separate and combined influences of dehydration and hyperthermia on cardiovascular responses to exercise - Gonzalez-Alonso, J. (International Journal of Sports Medicine, 1998)
During endurance exercise in the heat athletes lose 1-21/h of fluid due to thermoregulatory sweating. The ensuing dehydration is accompanied by higher and faster increases in core temperature, which per se can cause fatigue. The main cardiovascular consequences of combined dehydration and hyperthermia [1 degree C higher core temperature and 3-4 kg (4%) body weight loss] are the significant reductions in cardiac output (3 l/min), muscle blood flow, skin blood flow and blood pressure. Separately, however, hyperthermia (i.e., 39.3 C) and dehydration do not significantly reduce cardiac output or blood pressure. In conclusion, the superimposition of dehydration on hyperthermia during exercise in the heat causes greater alterations in cardiovascular function that make the dehydrated athlete much less able to cope with hyperthermia.